Setting Time Affects In Vitro Biological Properties of Root Canal Sealers - Camargo, Carlos Henrique R.; Oliveira, Tatiana R.; Silva, Gleyce O.; Rabelo, Sylvia B.; Valera, Marcia C.; Cavalcanti, Bruno N. (Elsevier, 2013)
Introduction: Biocompatibility of root canal sealers is important because of the long-term contact of their eluates and/or degradation products with periapical tissues. The literature still lacks studies about the genotoxic effects of these materials and the influence of setting time on biological properties. The cytotoxicity and genotoxicity of an epoxy resin-based sealer (AH Plus), a single methacrylate-based sealer (EndoRez), and a silicone-based sealer (RoekoSeal) were assessed. Methods: Chinese hamster fibroblasts (V79) were cultured and exposed to different dilutions of extracts from the sealers that were left to set for 0, 12, and 24 hours before contact with culture medium. Cell viability was measured by the methyl-thiazol-diphenyltetrazolium assay. Genotoxicity was assessed by the comet assay. Data were statistically analyzed by Kruskal-Wallis and Dunn tests (P < .05). Results: Root canal sealers were statistically more cytotoxic than the untreated control group, except for the silicon-based sealer. Cell viability ranking was the following (from the most to the least cytotoxic): methacrylate-based > epoxy resin-based > silicone-based. The setting time influenced the epoxy resin-based sealer cytotoxicity (decreased at 12 hours) and the general genotoxicity (increased at 24 hours). DNA damage ranking was the following (from the most to the least genotoxic): methacrylate-based > silicone-based = epoxy resin-based. Conclusions: The setting time had influence on the cytotoxicity of the epoxy resin-based sealer and genotoxicity of all tested sealers. The methacrylate-based sealer was the most cytotoxic, and the silicone-based sealer was not cytotoxic. Genotoxicity was observed for all sealers. © 2013 American Association of Endodontists.
Keywords: Biocompatibility; cytotoxicity; endodontic sealer; genotoxicity